A posição de garantidor de membros de órgãos colegiados em estruturas empresariais - Zonta, Fernando de Oliveira (2021)
This thesis aims to analyze the responsibility of the members of a corporate decision-making body for improper omission crimes, especially focusing on the guarantor position. This issue has been highlighted in recent years, especially due to the potential capacity of the institute of improper omission for the adequate handling of criminal responsibility within economic criminal law. In this way, we sought to establish solid theorical roots both on the interdisciplinary understanding of the company and its collective decision-making bodies, as well as on the criminal area that touches improper omission offenses, notably one of the components of the typical structure of improper omission crimes: the position of guarantor. In that regard, we concluded that accountability through the improper omission of members of corporate decision-making bodies is dogmatically possible, provided that the requirements for attribution are met. Therefore, under a materially founded aspect, the company can be considered a source of danger, which must be controlled and maintained within the acceptable parameters of risk so that no damage is caused to others' legal assets. Based on this premise, the responsibility for improper omission is founded on the risks arising from things and people, as well as on “interference”